Екскреція катехоламінів на тлі ожиріння у дитячому віці - Косовцова, Г. В. (Clinical Endocrinology and Endocrine Surgery, 2014)
The paper gives an analysis of the peculiarities in catecholamine (CA) urinary excretion in children and adolescents suffering from obesity in different age groups. Disorders in age-related dynamics of CA contents at the stages of puberty have been revealed both in boys and in girls with obesity due to activation of sympathoadrenal system (SAS) in 12-15 years. Persistent positive relationships between CA findings and the value of body mass index have been established in patients with obesity, in boys mainly due to dioxyphenilalanin (DOPA) and dophamin (DA), and in girls due to norepinephrine (NE) and epinephrine (EA). In girls with obesity, complicated with insulin resistance (IR), higher values of NE and E have been registered significantly more often. Growth of immunoreactive insulin and HOMA-IR index in obese boys is accompanied by an increased excretion of DA and NE. The data obtained, in general, are consistent with the findings of other researchers as regards SAS activation at early stages of puberty, which causes formation of other hormonal disorders and a rapid course of puberty in patients with obesity.